مستقبل النمو المهني لأعضاء هيئة التدريس بجامعة الكويت مدخل لبناء رأس المال الفكري من وجهة نظر الخبراء من القيادين في جامعة الكويت - الديحاني، سلطان غالب عوض (جامعة عين شمس - كلية التربية, 2016)
هدفت هذه الدراسة إلى بناء رؤية مستقبلية لتطوير النمو المهني لأعضاء هيئة التدريس بجامعة الكويت بوصفه مدخلا لبناء رأس المال الفكري لجامعة الكويت، وتحديد دور التنمية المهنية لأعضاء هيئة التدريس في بناء رأس المال الفكري في جامعة الكويت من وجهة نظر الخبراء من القياديين في جامعة الكويت، واعتمدت الدراسة على المنهجين: المنهج الوصفي والمنهج المستقبلي من خلال استخدام أسلوب دلفي، وتوصلت الدراسة إلى عدد من النتائج أهمها: 1. بناء رؤية مستقبلية لتطوير النمو المهني لأعضاء هيئة التدريس بجامعة الكويت بوصفه مدخلا لبناء رأس المال الفكري لجامعة الكويت. 2. وتحديد دور التنمية المهنية لأعضاء هيئة التدريس في بناء رأس المال الفكري في جامعة الكويت من خلال: استقطاب رأس المال الفكري -والمحافظة على رأس المال الفكري -وتنشيط رأس المال الفكري -وبناء رأس المال الفكري -وتنمية الاهتمام بالمستفيدين من المجتمع. 3. التعرف على التحديات التي تواجه تطبيق الرؤية المستقبلية لتطوير النمو المهني لأعضاء هيئة التدريس بجامعة الكويت بوصفه مدخلا لبناء رأس المال الفكري لجامعة الكويت.
This study aimed to build a future vision for the development of professional growth of faculty members at Kuwait University as an entry point to build the intellectual capital and to the Kuwait University, and to identify the role of professional development for faculty members in building intellectual capital and achieve competitive advantage at Kuwait University from the point of view of experts leaders at Kuwait University. The study relied on the descriptive approach and future approach by using of the Delphi method, the study found a number of findings, including: 1. building future vision for the development of professional growth of faculty members at the University of Kuwait as an entry point to build the intellectual capital and to achieve a competitive advantage to the University of Kuwait. 2. Define the role of the professional development of faculty members in the intellectual capital at Kuwait University building through: attracting intellectual capital, the preservation of intellectual capital, stimulate intellectual capital, building intellectual capital, and the development of attention beneficiaries of the community. 3. Recognize the challenges facing the implementation of the future vision for the development of professional growth of faculty members at the Kuwait University as an entry point to build the intellectual to the Kuwait University.
Keywords: السياسة التعليمية -- البرامج التعليمية -- التعليم الجامعي -- الوسائل التعليمية -- طلاب الجامعات -- جامعة الكويت -- أعضاء هيئة التدريس -- النمو المهني